ESTIMATION OF EXTREME RAINFALL INTENSITY-DURATION-FREQUENCY CURVE USING GLOBAL PRECIPITATION MEASUREMENT SATELLITE (CASE STUDY: JAVA ISLAND) - Regiandira Anggari, Delonix
Java Island is an area that often experiences hydromoteorological disasters, especially floods and landslides. Extreme rain was one of the dominant factors that caused the two disasters. This extreme rain can be analyzed using the Intensity-Duration-Frequency (IDF) curve. Chen (1983) formulated an equation that can estimate the complete IDF curve. Fauziah (2021) made modifications to Chen's (1983) method in order to combine the use of observation data and satellite data. The application of Chen's modification in western Java is still overestimated, so a test of the suitability of the duration function used in the Chen modification method is carried out using several other duration functions that have previously been applied in Java. The data used is Global Precipitation Measurement (GPM) satellite data for a duration of 30 minutes from 2000-2021. The IDF estimation equation used is a modified Chen equation whose duration function is substituted by the Sherman, Talbot, Ishiguro and Kimijima equations, while the rainfall intensity for various return periods (Tr) is estimated from the Gumbel frequency analysis (GEV I). The selection of the appropriate duration function equation is done by comparing the rainfall intensity from the estimation of various methods to the rainfall intensity from the Gumbel frequency analysis according to the value of the Root Mean Squared Error (RMSE). In general, the Chen-Sherman IDF estimation method is the most suitable method to be applied to all areas of Java Island, with RMSE values ranging from 0 – 2.12 mm/hour for all durations and return periods. The IDF estimation using the Chen-Talbot method is overestimated at a duration of < 150 hours, with an RMSE of 0.15 – 6.77 mm/hour, and is suitable to be applied in most areas of West and Central Java, as well as several areas in East Java. The Chen-Kimijima method is overestimated at all durations with an RMSE value of 0 – 9.8 mm/hour, and is suitable for application on the north coast of western Java, the central region of western Java, the majority of areas in East Java and the eastern coast of Java Island. The Chen-Ishiguro method is overestimated in all durations with RMSE values of 0 – 5.2 mm/hour and the majority is more suitable to be applied in the East Java region.